Errors in Pronouncing English in the English Department Students - Muhammad David Andikatama Putra; Iis Sujarwati (International Journal of Innovation and Education Research, 2023)
The aim of this study was to find out students’ errors in pronouncing vowel sounds which consisted of twelve sounds. The researcher used fourth-semester students of English Department at the University of Bengkulu. The method used in this research was descriptive qualitative because the researcher described about the students’ errors. Four students taken from three classes of English Department in academic year 2021/2022 WERE the sample used in this study. To collect the data, the researcher used a pronunciation test as the instrument. In analyzing the data, the researcher transcribed the recording in the form of phonetic transcription. As a result, the researcher found that students made errors in all of the vowel sounds. All of the students made error in pronouncing vocabularies with vowel sound /ɔ:/ and /ʊ/. Those errors are classified into three kinds of errors namely vowel length error, different English vowel sound system from Indonesian Vowel and students’ Wrong Pronunciation Acquisition. First, the students cannot differentiate the vowel length such as vowel /iː/ into vowel /ɪ/ and vice versa, vowel /u:/ to vowel /ʊ/, vowel /ɜː/ into vowel /e/ and vowel sound /Ʌ/ into /ɑ:/. Second, the students substituted the vowel /æ/ into vowel /e/ and vowel sound /ә/ into /e/ or vice versa because there is no vowel sounds such as /æ/ and /ә/ in Indonesian. Last, the students substituted the vowel /ɔː/ into /ɑ:/ and vowel /ʊ/ into vowel /ə/ where they were actually different but the students considered that it was true.